History of Hand Hygiene Increases Undergraduate Nursing Students’ Positive Attitude Toward Hand Hygiene Practice (International Journal of Nursing Education, 2022)
Various media on hand hygiene topics have been developed to make it easier for students to master theprocedure, but positive attitudes toward applying these skills have not significantly developed. The study aimedto determine the effect of hand hygiene history on undergraduate nursing students’ attitudes to hand hygiene. Aquasi-experiment using a pre-and post-test with a control group design was conducted. Fifty-four students wereinvited and randomly assigned to an intervention group and a control group. The intervention group obtainedthe hand hygiene history through a booklet, while the control group got no treatment. The data were collectedusing a questionnaire. The paired and unpaired t-test was applied to analyze the data. The results showedthat the average score of students’ attitudes in the intervention group increased from 58.44±5.98 to 65.52±5.29(p
Keywords: Attitude, Hand hygiene; nursing student; the history of hand hygiene.